Cellular mechanisms underlying the rapid depolarization caused by oxygen and glucose deprivation in layer III pyramidal cells of the somatosensory cortex. (March 2021) - Toyoda, Hiroki; Kawano, Tsutomu; Sato, Hajime; Kato, Takafumi
Highlights: Oxygen-glucose deprivation (OGD) causes rapid membrane depolarization. OGD-induced intracellular Ca 2+ rises contribute to generation of rapid depolarization. OGD-induced NO and ROS production contributes to generation of rapid depolarization. Dysfunction of Na + -K + -ATPase contributes to generation of rapid depolarization. Abstract: Cortical pyramidal neurons show rapid and irreversible membrane depolarization in response to oxygen-glucose depolarization (OGD). In this study, we investigated cellular mechanisms responsible for rapid depolarization caused by OGD in layer III pyramidal neurons of the mouse somatosensory cortex. When OGD solution was perfused in the presence of Ca 2+ chelator and inhibitors of ryanodine receptors (RyRs) and inositol 1, 4, 5-trisphosphate receptors (IP3 Rs) in the pipette solution or in the presence of inhibitors of NMDA receptors (NMDARs), voltage-gated Ca 2+ channels (VGCCs), and canonical transient receptor potential (TRPC) channels in the perfusion solution, the latency of the rapid depolarization was significantly prolonged compared to the control. In addition, when OGD solution was perfused in the presence of scavengers of nitric oxide and reactive oxygen species in the perfusion solution or in the presence of calcineurin inhibitors in the pipette solution, the latency of the rapid depolarization was significantly prolonged compared to the control. These data indicate that OGD-induced intracellular Ca 2+ increases mediated by Ca 2+ influx through NMDARs, VGCCs and TRPC channels as well as by Ca 2+ release from RyRs and IP3 Rs lead to mitochondrial impairment, which may facilitate the generation of the rapid depolarization via dysfunction of Na + -K + -ATPase due to decreased ATP production.